344 THE ROLE OF TRPV2 IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (17th September 2021) - Kato, Shunji; Shiozaki, Atsushi; Fujiwara, Hitoshi; Konishi, Hirotaka; Kudou, Michihiro; Yamazato, Yuzo; Katsurahara, Keita; Shoda, Katsutoshi; Arita, Tomohiro; Kosuga, Toshiyuki; Komatsu, Shuhei; Kubota, Takeshi; et al.
Abstract: : Transient receptor potential vanilloid 2 (TRPV2) was recently shown to be involved in migrant potentials. Previous studies reported that TRPV2 was involved in cancer progression, migration, and invasion. The present study aimed to investigate its role in esophageal squamous cell carcinoma (ESCC). Methods: In human ESCC cell lines, we investigated the role of TPRV2 in ESCC using a cancer function assay with the knockdown of TRPV2 by siRNA, microarray, pathway, and gene ontology analyses. The significance of TRPV2 expression in 62 ESCC samples was then evaluated by immunohistochemical staining. Results: TRPV2 was overexpressed in TE15 and KYSE170 cells. TRPV2 depletion suppressed cell proliferation, cell cycle progression, and invasion/migration, and induced apoptosis. A pathway analysis of microarray data revealed that TRPV2 depletion down-regulated WNT/β-catenin signaling-related genes and basal cell carcinoma signaling-related genes. The suppression of cancer functions, such as proliferation, invasion, and angiogenesis, by TRPV2 depletion was predicted in the ontology analysis. Immunohistochemical staining revealed a relationship between strong TRPV2 expression and a poor prognosis in ESCC patients. Conclusion: The present results suggest that TRPV2 regulates tumor progression by affecting WNT/β-catenin or basal cell carcinoma signaling, and that its strong expression is associated with a worse prognosis in ESCC patients. These results provide an insight into the role of TRPV2 as a therapeutic target or biomarker for ESCC.